A review of microalgae and other treatment methods of distillery wastewater. (16th April 2020) - Amenorfenyo, David Kwame; Huang, Xianghu; Li, Changling; Li, Feng; Zeng, Qitao; Zhang, Ning; Xie, Lishi; Wang, Peiming
Abstract: Many industries including distilleries continue to contribute to environmental pollution due to significant release of organic and inorganic pollutants as wastewater. This wastewater contains heavy metals and other toxic chemicals that lead to health‐related problems. Despite the advancement in treatment technologies, major treatment methods such as conventional treatment methods are still battering with the many challenges including high treatment and operational cost, and extensive use of chemicals that may lead to ecological imbalance. In this study, various treatment methods and pollutants removal capabilities were comprehensively discussed. This article also takes a comprehensive look at the alcohol production process and its wastewater generation, chemical characteristics and the health dangers posed by the distillery wastewater (DW). The article also looked at the various available treatment methods, emerging treatment methods, microalgae treatment method as well as challenges associated with microalgae wastewater treatment.